Sarcopenia Is Associated With a Risk of Mortality in People With Type 2 Diabetes Mellitus - Fuyuko Takahashi (Frontiers Media S.A., 2021)
BackgroundSarcopenia has reportedly been associated with increased risk of mortality in general populations. However, few studies have investigated the association between sarcopenia and mortality in older people with type 2 diabetes mellitus (T2D). This study aimed to investigate the effect of sarcopenia on incident all-cause mortality in older people with T2D.MethodsLow muscle strength were set at handgrip strength <28 kg for men and <18 kg for women, and low skeletal muscle mass index (SMI), evaluated using the impedance body composition analyzer, were set at SMI <7.0 kg/m2 for men and <5.7 kg/m2 for women. People who had both low muscle strength and low SMI were diagnosed with sarcopenia. Due to a low incidence of all-cause mortality, the propensity score was used. The propensity score was evaluated using multivariable logistic regression models with the following parameters: age, sex, duration of diabetes, history of heart disease, history of cancer, smoking, exercise, alcohol, sodium-glucose cotransporter-2 inhibitor, glucagon-like peptide-1 receptor agonist, insulin, corticosteroid, hypertension, body mass index, glycosylated hemoglobin A1c, triglycerides, and creatinine, and the C-statistic was 0.89.ResultsIn this prospective cohort study, 396 people with an average age and duration of diabetes of 71.3 (6.3) years and 16.3 (11.3) years, respectively, were included. Of those included, 14.6% had sarcopenia. During the average 40.5 (16.5) months of follow-up, 13 people (6 out of the 338 without sarcopenia and 7 out of the 58 with sarcopenia) died. Incident rate were 5.1/1000 person years of follow-up in people without sarcopenia and 41.3/1000 person years of follow-up in people with sarcopenia. According to Cox regression analysis, sarcopenia was associated with all-cause mortality (adjusted hazard ratio: 6.12, 95% confidence interval: 1.52–24.7, p = 0.011).ConclusionSarcopenia is associated with incident all-cause mortality in older outpatients with T2D.